Biodiesel production intensification through microbubble mediated esterification. (1st October 2019) - Ahmad, Naveed; Javed, Fahed; Awan, Javeed Ashraf; Ali, Shahzad; Fazal, Tahir; Hafeez, Ainy; Aslam, Rabya; Rashid, Naim; Rehman, Muhammad Saif Ur; Zimmerman, William B.; Rehman, Fahad
Graphical abstract: Highlights: Manipulating equilibrium can convert the reversible reaction to irreversible reaction. Reaction at the skin of the bubble is kinetically dominating step in esterification process. Achieved 97% conversion in 35 min. Abstract: Depleting fossil fuel resources and related environmental concerns have focused the world's attention on finding sustainable and renewable energy resources such as biofuels. Biodiesel, produced from vegetable oil, animal fats, waste cooking oil, and greases, shows a promising alternative for petroleum-diesel. The conventional biodiesel production methods are time consuming and energy intensive due to mass transfer limitations. This limitation can be reduced by carrying out reaction at a bubble interface which supplies a "local" excess of alcohol to push equilibrium in the forward direction while simultaneously increasing the rate of reaction. During this process, methanol vapors, fed through a sintered borosilicate diffuser, react with the free fatty acids (oleic acid in this case) and catalyst. Owing to the lower flow rates of methanol and pore size of the diffuser (15–40 μm) used, the bubbles produced are significantly smaller 1 mm and lies in the range of 200–600 μm. Kinetic study shows that reaction follows first order kinetics w.r.t. oleic acid. The esterification reaction through bubble reactor achieved 97% conversion of oleic acid in 30 min as compared with 80% in 312 min using conventional methods.